The events of yesterday and today: a show of power - Mut Camacho, Magdalena; Bernad Monferrer, Estela (Historia y Comunicación Social, 2014)
The event today is a kind of communication where the ultimate goal is the emotional connection between the company and the public. This is an overall experience where everything communicates, It have the power to communicate through feelings, they are spaces where information lives, feel and touch. Therefore, one can derive that the events are tools used efficiently and creatively, have power and they are a demonstration of power . This technique of communication is not new. If we turn to history, we find the demonstration of power and wealth were the events and who made them were kings. Today, it is the company that has collected this intention and uses the event with the same ultimate goal , demonstrate power, get dazzle and thrill audiences who flock.